2011
DOI: 10.5402/2011/402906
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Anesthetic Toxicity: Metabolism, Reactive Oxygen Species, Oxidative Stress, and Electron Transfer

Abstract: There is much literature on the toxic effects of anesthetics. This paper deals with both the volatiles and locals. Adverse effects appear to be multifaceted, with the focus on radicals, oxidative stress (OS), and electron transfer (ET). ET functionalities involved are quinone, iminoquinone, conjugated iminium, and nitrone. The non-ET routes involving radicals and OS apparently pertain to haloalkanes and ethers. Beneficial effects of antioxidants, evidently countering OS, are reported. Knowledge at the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…Moreover, these results could support the causative role of the systemic transfer of LA in the suspected shift from pro‐oxidative to antioxidative homeostasis. This shift seems to be linked to the overproduction of ROS and the depleted stores of antioxidant species . Similar results have been reported in the course of myocardial ischemia .…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, these results could support the causative role of the systemic transfer of LA in the suspected shift from pro‐oxidative to antioxidative homeostasis. This shift seems to be linked to the overproduction of ROS and the depleted stores of antioxidant species . Similar results have been reported in the course of myocardial ischemia .…”
Section: Discussionsupporting
confidence: 85%
“…Although propofol, which is chemically similar to endogenous vitamin E, has been reported to have antioxidant properties [19], no such effects could be confi rmed from this study, and total intravenous anaesthesia with propofol alone was not found to be superior to propofol/sevofl urane anaesthesia in this regard. The plasma concentration of vitamin E decreased after induction to anaesthesia in the propofol group and during anaesthesia in both groups, which might be a consequence of vitamin E consumption due to increased production of ROS during anaesthesia [20]. Naziroǧlu and Günay [21] also reported a signifi cant decrease in serum vitamin E concentrations in healthy dogs anaesthetized with enfl urane.…”
Section: Discussionmentioning
confidence: 90%
“…In the plasma of healthy men, vitamin E represents up to 75% of ACL [16,17]. A decrease in vitamin E (total tocopherol) during anaesthesia was demonstrated in dogs with MMVD [18], healthy dogs [19] and people [20,21], as well as a decrease in alpha tocopherol in people [22,23].Metabolism of anaesthetics and changes in tissue oxygenation during anaesthesia promote increased formation of ROS, which affects antioxidant defence system [7,24,25].…”
Section: Discussionmentioning
confidence: 99%